2013
DOI: 10.3109/00365548.2013.804631
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pneumococcal pneumonia diagnostics by the use of rt-PCR on plasma and respiratory samples

Abstract: rt-PCR on plasma and other samples performed significantly better than culture for the detection of pneumococcal pneumonia (p < 0.0005) in children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…The South African study also used serum rather than whole blood [10]. In Slovenia, pneumococcal PCR was positive from plasma in 2 of 29 (6.9%) children with a nonpneumonia acute febrile illness for which a nonpneumococcal cause was identified [19]. Both of the children who tested positive were colonized with pneumococcus.…”
Section: Discussionmentioning
confidence: 99%
“…The South African study also used serum rather than whole blood [10]. In Slovenia, pneumococcal PCR was positive from plasma in 2 of 29 (6.9%) children with a nonpneumonia acute febrile illness for which a nonpneumococcal cause was identified [19]. Both of the children who tested positive were colonized with pneumococcus.…”
Section: Discussionmentioning
confidence: 99%
“…106 Several studies have described substantially enhanced detection of S pneumoniae in blood samples using real time PCR targeting the lytA gene of the pneumococcus, compared with blood culture. [107][108][109] However recent results from the multicenter Pneumonia Etiology Research for Child Health (PERCH) study showed both poor sensitivity (64%; 36/56 microbiologically confirmed pneumococcal pneumonia cases were PCR positive) and specificity (5.5%; 273/4987 of non-pneumonia controls were PCR positive). 110 These results illustrate the need for Reducing contamination of samples Samples that are less likely to be contaminated by upper respiratory flora may be less prone to problems of interpretation.…”
Section: Value Of Different Specimen Types and Associated Diagnostic mentioning
confidence: 99%
“…Serological testing of blood specimens may be useful for epidemiological studies of the cause of pneumonia, where comparison of acute and convalescent titers may help identify the causative agent, [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] although the diagnostic value of a single specimen collected in the acute phase of the illness is generally limited. Pertussis serology may be a useful complementary diagnostic tool in older children and during the later phases of illness.…”
Section: Emerging Diagnosticsmentioning
confidence: 99%
“…The identification of S. pneumoniae can be significantly improved by using molecular biology methods which, albeit with some exceptions, have been found to be significantly more reliable than the traditional non-enriched cultures used in routine practice 59 and, although S. pneumoniae is bet sampled nasopharyngeally in infants and young children, 60 recent studies have shown that oropharyngeal sampling is better in older children, adolescents and adults. 61,62 Finally, it is still unclear exactly when the effect of a vaccine on carriage should be evaluated.…”
Section: Main Limitationsmentioning
confidence: 99%